Reanalysis for local quantities of interest - Materna, Daniel (Proceedings in applied mathematics and mechanics : PAMM)
In this contribution a method for the prediction of the change in a quantity of interest due to structural modifications is considered. The approach is based on a goal-oriented method by using the primal and dual problems. The method can be used in order to reduce the overall computational cost in the numerical simulation. Furthermore, the proposed method is easily to implement in existing finite element programs, because no derivatives with respect to the design variables are necessary.